The association between measurements of external load and bone structural characteristics in elite cricketers and football players. - Scott, R.; Sale, C.; James, R.; Barnett, C.; Varley, I. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Despite exercise being prescribed to benefit bone health [1], little is known about the specific external loading characteristics of exercise required to promote bone accrual. It Is not known how limb specific loading variables are associated with bone characteristics. We aimed to assess if quantified external loading is associated with tibial bone characteristics in elite cricketers and football players.